DESCRIPTION OF EXPERIMENTAL DEVICES IN GREENHOUSES AND EVALUATION OF ERRORS OF MEASUREMENT CONTROL DEVICES - AIlkhom Pirnazarov Islamovich; Sobirjon Boboyev Muradullayevich (Web of Journals Publishing, 2024)
Is to create energy-efficient hot air distribution equipment in order to ensure optimal microclimate conditions for the cultivation of organic genuine agriculture (fruit and vegetable) products in greenhouses.